Bone marrow necrosis in malignant diseases. A report on seven intravitally recognized cases - Scudla, V; Dusek, J; Macák, J; Zivná, J; Myslivecek, M; Indrák, K (Neoplasma, 1989)
Bone marrow necrosis (BMN) is a necrosis of the hemopoietic tissue including the fibrovascular medullary stroma. Most frequently, it is caused by failure of bone marrow microcirculation. It is a complication in a wide spectrum of diseases, most frequently of malignancies, and is only rarely diagnosed ante mortem. In 6 of our 7 intravitally diagnosed cases, BMN was recognized already at the cytological examination of the bone marrow and was verified by the histological examination of the biopsy specimens as well as at necropsy. All our patients suffered from various malignant diseases. Three had generalized gastric carcinoma, the remaining hematological neoplasias: Acute lymphoblastic leukemia, acute monocytic leukemia, blastic transformation of chronic granulomegakaryocytic myelosis and primary medullary centrocytic lymphoma. The survival varied from 4 to 14 weeks after the BMN diagnosis. Clinical, hematological and autopsy findings as well as the etiopathogenetic views and prognostic implications of the diagnosis are discussed.
Keywords: bolest; Pain; Biopsy; Bone Marrow; krevní obraz; Humans; lidé středního věku; nemoci kostní dřeně; nekróza; Autopsy; Female; dospělí; pitva; lidé; Bone Marrow Diseases; biopsie; Adult; Blood Cell Count; ženské pohlaví; Male; Middle Aged; prognóza; kostní dřeň; Neoplasms; Anemia; anemie; nádory; Radionuclide Imaging; mužské pohlaví; radioisotopová scintigrafie; Necrosis; Prognosis